Fabricate optical microfiber by using flame brushing technique and coated with polymer polyaniline for sensing application - Razak, Nazrul; Hamida, Belal Ahmed; Irawati, Ninik; Habaebi, Mohamed Hadi (IOP Publishing, 2017)
Adiabaticity is one of the essential criteria in producing good fabricated tapered fibers. Good tapered fibers can be use in sensor application such as humidity sensor, temperature sensor and refractive index sensor. In this paper, good tapering silica fiber is produced by using flame brushing technique and then, the microfiber is coated with polymer Polyaniline (PAni) to sense different type of alcohols with different concentrations. The outcome of this experiment gives excellent repeatability in the detection of alcohol sensing with a sensitivity of 0.1332 μW/% and a resolution of 3.764%. In conclusion, conducting polymer coated optical microfiber sensor for alcohol detection with low cost, effective and simple set-up was successfully achieved in this study.